Physiologic Responses to Infrarenal Aortic Cross-Clamping during Laparoscopic or Conventional Vascular Surgery in Experimental Animal Model: Comparative Study - María F. Martín-Cancho; Verónica Crisóstomo; Federico Soria; Carmen Calles; Francisco M. Sánchez-Margallo; Idoia Díaz-Güemes; Jesús Usón-Gargallo (Anesthesiology Research and Practice)
The aim of this study was to compare the hemodynamic and ventilatory effects of prolonged infrarenal aortic cross-clamping in pigs undergoing either laparotomy or laparoscopy. 18 pigs were used for this study. Infrarenal aortic crossclamping was performed for 60 minutes in groups I (laparotomy, n=6) and II (laparoscopy, n=6). Group III (laparoscopy, n=6) underwent a 120-minute long pneumoperitoneum in absence of aortic clamping (sham group). Ventilatory and hemodynamic parameters and renal function were serially determined in all groups. A significant decrease in pH and significant increase in PaCO2 were observed in group II, whereas no changes in these parameters were seen in group I and III. All variables returned to values similar to baseline in groups I and II 60 minutes after declamping. A significant increase in renal resistive index was evidenced during laparoscopy, with significantly higher values seen in Group II. Thus a synergic effect of pneumoperitoneum and aortic cross-clamping was seen in this study. These two factors together cause decreased renal perfusion and acidosis, thus negatively affecting the patient's general state during this type of surgery.